2017
DOI: 10.1016/j.celrep.2017.03.053
|View full text |Cite
|
Sign up to set email alerts
|

IDH1 Mutation Promotes Tumorigenesis by Inhibiting JNK Activation and Apoptosis Induced by Serum Starvation

Abstract: Two hallmarks of cancer cells are their resistance to apoptosis and ability to thrive despite reduced levels of vital serum components. c-jun N-terminal kinase (JNK) activation is crucial for apoptosis triggered by serum starvation (SS), and isocitrate dehydrogenase 1 (IDH1) mutations are tumorigenic, in part, because they produce the abnormal metabolite 2-hydroxyglutarate (2-HG). However, it is unknown whether 2-HG-induced tumorigenesis is partially due to JNK inhibition and thus defective SS-induced apoptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…Since the tumour microenvironment has an extremely low supply of serum components caused by the uncontrolled proliferation of malignant tumours, serum starvation can be used to simulate this barren microenvironment and thus observe the special mechanisms involved in the anti-apoptotic action of malignant tumours. 35 After 48 hours of serum starvation, a large proportion of MNNG/HOS cells were able to tolerate this barren simulated tumour microenvironment, while blocking the MALAT1/EZH2 axis could lead to maladjustment (Fig. 1 E).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Since the tumour microenvironment has an extremely low supply of serum components caused by the uncontrolled proliferation of malignant tumours, serum starvation can be used to simulate this barren microenvironment and thus observe the special mechanisms involved in the anti-apoptotic action of malignant tumours. 35 After 48 hours of serum starvation, a large proportion of MNNG/HOS cells were able to tolerate this barren simulated tumour microenvironment, while blocking the MALAT1/EZH2 axis could lead to maladjustment (Fig. 1 E).…”
Section: Resultsmentioning
confidence: 97%
“…The microenvironment of malignant tumours is extremely lacking in serum components, because of uncontrolled proliferation. 35 Hence, we used serum starvation to investigate the effect of this low-nutrient microenvironment on OS cells. We also found that siMALAT1 could promote cell apoptosis not only in the simulated environment in vitro but also in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…D-2-HG was found to be able to competitively inhibit SDH resulting in the accumulation of succinate, increased protein hypersuccinylation, and impairment of mitochondrial respiration [ 100 ]. In addition, 2-HG has been reported to bind the DNA methyltransferase DNMT1 and the small GTPase Cdc42, although neither enzyme binds α-KG [ 101 , 102 ]. 2-HG stimulated DNMT1 to bind the promoter and repress the expression of receptor-interacting protein kinase 3 (RIP3), a regulator of programmed necrosis/necroptosis, suggesting that impaired RIP3-dependent necroptosis may contribute to tumorigenesis driven by IDH mutation [ 102 ].…”
Section: -Hg Activity Beyond Epigenetic Alterationmentioning
confidence: 99%
“…2-HG stimulated DNMT1 to bind the promoter and repress the expression of receptor-interacting protein kinase 3 (RIP3), a regulator of programmed necrosis/necroptosis, suggesting that impaired RIP3-dependent necroptosis may contribute to tumorigenesis driven by IDH mutation [ 102 ]. Binding of 2-HG to Cdc42 disrupted Cdc42’s association with the effector mixed lineage kinase 3 (MLK3), leading to suppression of MLK3 activation and MLK3-mediated apoptosis in serum-deprived mutant IDH1 cells [ 101 ]. Future genetic and biophysical characterizations are necessary to understand the significance and affinities of 2-HG binding to DNMT1 and Cdc42.…”
Section: -Hg Activity Beyond Epigenetic Alterationmentioning
confidence: 99%
“…As the TME is characterized by both high metabolic rate and relatively low serum components due to abnormal proliferation, serum starvation is another frequently used method for evaluating the anti‐apoptotic activity and viability of malignant tumors. [ 5b,40 ]…”
Section: Discussionmentioning
confidence: 99%